NEUROSISTISERKOSIS INTRAVENTRIKULAR DENGAN TERAPI PEMBEDAHAN - Jackson Sihombing,* Wayan Niryana,** Ni Made Susilawathi,** Anak Agung Raka Sudewi** (NEURONA, 2017)
NCC IS A PARASITIC INFECTION OF THE BRAIN CAUSED BY LARVAE OF TAENIA SOLIUM IN THE FORM OF CYSTS CYSTISCERCUS INTRAPARENKIM IS OFTEN TO BE FOUND IN THE BRAIN WHEREAS INTRAVENTRICULAR OR SUBARACHNOID RARELY OCCUR 1530 INTRAVENTRICULAR LESION OFTEN CAUSE SYMPTOMS OF HYDROCEPHALUS THUS RISK OF FATAL COMPLICATIONS THIS REQUIRES COMPLEX HANDLING WITH SURGICAL THERAPY